Hypokalemic quadriparesis associated with renal tubular acidosis in a patient with Sjögren's syndrome - Aygen, B.; Dursun, F.E.; Dogukan, A.; Ozercan, I.H.; Celiker, H. (Dustri-Verlag Dr. Karl Feistle, 2008)
Sjögren's syndrome is an autoimmune exocrinopathy that involves both glandular and extra-glandular systems. We report a 25-year-old woman who had rapidly progressive quadriparesis. Biochemical investigations showed severe hypokalemia, with hyperchloremic metabolic acidosis diagnosed as distal renal tubular acidosis. Salivary gland biopsy revealed Sjögren's syndrome as the underlying cause. She recovered following from quadriparesis potassium and alkali replacement.
Keywords: Hypokalemia; Quadriparesis; Sjögren's syndrome